MiR-4270 acts as a tumor suppressor by directly targeting Bcl-xL in human osteosarcoma cells - Veys, Clément; Boulouard, Flavie; Benmoussa, Abderrahim; Jammes, Manon; Brotin, Emilie; Rédini, Françoise; Poulain, Laurent; Gruchy, Nicolas; Denoyelle, Christophe; Legendre, Florence; Galera, Philippe (Frontiers in Oncology, 2023)
Chondrosarcomas and osteosarcomas are malignant bone tumors with a poor prognosis when unresectable or metastasized. Moreover, radiotherapy and chemotherapy could be ineffective. MiRNAs represent an alternative therapeutic approach. Based on high-throughput functional screening, we identified four miRNAs with a potential antiproliferative effect on SW1353 chondrosarcoma cells. Individual functional validations were then performed in SW1353 cells, as well as in three osteosarcoma cell lines. The antiproliferative and cytotoxic effects of miRNAs were evaluated in comparison with a positive control, miR-342-5p. Then, cell cycle phase distribution was analyzed using flow cytometry. Western-blots and luciferase reporter assays were carried out to determine the mechanisms of action of the cytotoxic miRNAs. The cytotoxic effect of four selected miRNAs was not confirmed on SW1353 cells, but we unambiguously revealed that miR-4270 had a potent cytotoxic effect on HOS and MG-63 osteosarcoma cell lines, but not on SaOS-2 cell line. Furthermore, like miR-342-5p, miR-4270 induced apoptosis in these two cell lines. In addition, we This is a provisional file, not the final typeset article provided the first report of Bcl-xL as a direct target of miR-4270. MiR-4270 also decreased the expression of the anti-apoptotic protein Mcl-1, and increased the expression of the pro-apoptotic protein Bak. Our findings demonstrated that miR-4270 has tumor suppressive activity in osteosarcoma cells, particularly through Bcl-xL downregulation. involving the regulation of the expression of Bcl-2 family proteins.